2021
DOI: 10.1002/jcsm.12734
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and preserved bone mineral density in paediatric survivors of high‐risk neuroblastoma with growth failure

Abstract: Background Survival from paediatric high‐risk neuroblastoma (HR‐NBL) has increased, but cis‐retinoic acid (cis‐RA), the cornerstone of HR‐NBL therapy, can cause osteoporosis and premature physeal closure and is a potential threat to skeletal structure in HR‐NBL survivors. Sarcopenia is associated with increased morbidity in survivors of paediatric malignancies. Low muscle mass may be associated with poor prognosis in HR‐NBL patients but has not been studied in these survivors. The study objective was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…Other studies 3 , 13 , 14 demonstrated that skeletal muscle improved bone health and fat was harmful to bone density, similar to our findings that SMM or FFM exhibited a linear positive correlation with BMD and BFM with a negative correlation with BMD ( Figure 3 ). Interestingly, the whole BFM further divided into trunk BFM and non-trunk BFM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies 3 , 13 , 14 demonstrated that skeletal muscle improved bone health and fat was harmful to bone density, similar to our findings that SMM or FFM exhibited a linear positive correlation with BMD and BFM with a negative correlation with BMD ( Figure 3 ). Interestingly, the whole BFM further divided into trunk BFM and non-trunk BFM.…”
Section: Discussionsupporting
confidence: 91%
“…Further, few data are available on individuals with type two diabetes (T2DM), though the relationship between BMD and body composition has been widely discussed in children, the elderly and obesity. 3 , 13 , 14 This is in that fragility fractures have been recognized as a crucial diabetes complication. 15 Hence, and the novelty of our study is that we firstly observe the combined effect of muscle-fat on BMD with novel non-linear covariate-adjusted penalized spline generalized additive models (GAMs) in specific T2DM individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 ] demonstrated the loss in appendicular LSTM Index in boys with Duchenne’s muscular dystrophy, and Guo et al. [ 36 ] reported more pronounced deficits in appendicular LSTM Index (compared to total LSTM Index) in survivors of neuroblastoma. Of note, we included reference ranges for total LSTM Index and subtotal LSTM Index in supplementary tables because appendicular LSTM may not be available to all clinicians or investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive techniques: skinfold, bio-electric impedance analysis (BIA) [15]; ultrasound [16], creatine excretion [17], total or partial body potassium per fat-free soft tissue [18], and neutron activation [19] • Two-component techniques and models: dual-energy x-ray absorptiometry (DXA) (Figure 1) [20,21], air displacement plethysmography [22][23][24], deuterium dilution [25], computed tomography (CT) [21,26], and magnetic resonance imaging (MRI) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Predictive techniques: skinfold, bio-electric impedance analysis (BIA) [15 sound [16], creatine excretion [17], total or partial body potassium per fattissue [18], and neutron activation [19] • Two-component techniques and models: dual-energy x-ray absorptiometr (Figure 1) [20,21], air displacement plethysmography [22][23][24], deuterium [25], computed tomography (CT) [21,26], and magnetic resonance imagin [27,28]. While in adults, Baumgartner et al [29] proposed using Dual-energy X-ray tiometry (DXA) and bioelectrical impedance analysis (BIA) as standardized me determine lean body mass, comparing values obtained to a normal referenced po (gender-specific young adult), no such methods are uniformly adopted for chil cause of ongoing changes in body composition during childhood [15].…”
mentioning
confidence: 99%